Concept NADEZHDA (HOPE) in Russian and Chinese Language Pictures of the World in the Aspect of Contrastive Linguo-Culturological Analysis - C. Chang (Научный диалог, 2018)
The article presents contrastive linguo-culturological analysis of the unique Russian cultural concept NADEZHDA (HOPE) and the corresponding Chinese one. The purpose is to give complex description of content and structure features of verbal embodiment of the concept NADEZHDA in the aspect of Russian-Chinese language correlations. Design / methodology / approach include the following. The linguo-culturological approach is the base of the research methodology. The concrete method is the methodic of contrastive linguo-culturological analysis of conceptual content and language objectification of the concept. The material of the study is the data of basic Russian and Chinese dictionaries. Practical implications of the research are conditioned by possibility to use its results for teaching Russian as foreign language for Chinese graduate and post-graduate students. The results can be also used in the theory and practice of compiling the innovational dictionaries of concepts and linguo-cultural thesauri. Findings are that all the sense components of the Russian cultural concept the concept NADEZHDA are mainly presented in Chinese, but they are realized in different, diverged semantically and historically words. If the Russian concept NADEZHDA goes back to the idea of a stronghold, a support, the Chinese concept accents prospective semantics on the basis of spatial representations. Different cultural realities of Russian and Chinese worlds are expected to be reflected in language embodiment of compared concepts. Originality / value consists in that the analysis proves that the Russian concept NADEZHDA is connected with the other concepts VERA (FAITH) and SUD’BA (DESTINY) together with them expressing the key idea of the Russian language picture of the world about unpredictability of the universe, while the Chinese concept is corresponded with the idea of Middle Way and moderation, it is mainly oriented to the concept NORM.